Passive Positioning and Adjustment Strategy for UAV Swarm Considering Formation Electromagnetic Compatibility - Junjie Huang; Lei Zhang; Wenqian Wang (Drones)
In recent years, UAV formations have garnered significant attention in fields such as reconnaissance, communications, and transportation. This paper aims to design an efficient passive localization method for UAV formations that satisfies system electromagnetic compatibility (EMC) requirements. A self-adjustment model characterized by internally active communication and externally silent operation for UAV formations is proposed, which optimizes the positions of the UAVs under test based on their current locations and standard reference positions while adhering to formation geometry constraints. By comprehensively considering constraints including the number of UAVs, formation geometry, and system EMC, this study evaluates electromagnetic radiation interference within the UAV formation system and derives an iterative adjustment scheme for formation positions. Finally, simulation experiments through specific case studies calculate polar radius deviations and polar angle deviations during the adjustment process. The results validate that the proposed method meets the requirements for both formation adjustment and EMC, thereby providing a more scientific basis for passive localization and position adjustment in UAV formations.